Accounting association of the European area - Prelić Jovan; Nešić Branko; Gajić Tamara (Oditor, 2018)
Understanding that priority activities of national and international accounting institutions should be in the process of establishing and building accounting principles and standards (these principles and standards must be observed by companies when compiling financial statements, in order to ensure proper accountability and provide the necessary comparability, as well as in terms of comparing the audit technique and methodology, so that the verified financial statements become the necessary information base for all shareholders ) was mostly affected by the fact that the financial statements are an indispensable information basis for users of accounting information (internal and external), in assessing the company's financial, financial and viability position. As a result of the need for harmonization of accounting satellites in America and Europe, a large number of associations have been formed, and the scope of work and the activities carried out by these associations are shown in the work itself.